PENGEMBANGAN E-MODUL PENCEGAHAN KEKERASAN DI SEKOLAH DASAR - Ibrahim, Yuniar Marhamah S.; Pulukadang, Wiwy Triyanty; Ismail, Reska Putri; Husain, Rusmin; Cuga, Candra (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Development of Violence Prevention E-Module in Elementary Schools. This study aims to prevent acts of violence that are expected to be able to prevent behavior related to bullying, sexual violence, and intolerance to improve the quality of education. The research method used is the research and development method (Research and Development) using the Thiagarajan research and development model, namely Define, Design, Development, and Dissemination. However, this study only reached the development stage. The objectives of this study are 1). To determine the analysis of the needs of the E-Module for preventing violence in Elementary Schools, 2). To determine the design of the E-Module for preventing violence, 3). To determine the development of the E-Module for preventing violence in Elementary Schools, 4). To determine the impact of the E-Module for preventing violence in Elementary School 3 Tilango. Based on the results of validation by experts and users, namely, obtaining a recapitulation of the average percentage value of 95.72% and declared very suitable for use by teachers as facilitators and students in Elementary Schools. The results of the limited trial (process test) carried out in class V of Elementary School 3 Tilango obtained very good results from both teachers and students. Thus, the results of the development of the E-Module for Prevention of Violence in Elementary Schools are stated to be very feasible to use, and are believed to be able to prevent bullying behavior, sexual violence, and intolerance, to improve the quality of education. ABSTRAKPengembangan E-Modul Pencegahan Kekerasan di Sekolah Dasar. Penelitian ini bertujuan untuk mencegah tindak kekerasan yang diharapkan mampu mencegah perilaku terkait perundungan, kekerasan seksual, dan intoleransi untuk peningkatan kualitas pendidikan. Metode penelitian yang digunakan adalah metode penelitian pengembangan (Research and Development) dengan menggunakan model penelitian pengembangan Thiagarajan yaitu Define, Design, Development, dan Dissemination. Akan tetapi, penelitian ini hanya sampai pada tahap development (pengembangan). Adapun tujuan penelitian ini adalah 1). Mengetahui analisis kebutuhan E-Modul pencegahan kekerasan di Sekolah Dasar, 2). Mengetahui desain E-Modul pencegahan kekerasan, 3). Mengetahui pengembangan E-Modul pencegahan kekerasan di Sekolah Dasar, 4). Mengetahui dampak E-Modul pencegahan kekerasan di SD Negeri 3 Tilango. Berdasarkan hasil validasi oleh para ahli dan pengguna yakni, memperoleh hasil rekapitulasi nilai rata-rata persentase 95,72% dan dinyatakan sangat layak digunakan oleh guru sebagai fasilitator dan peserta didik di Sekolah Dasar. Adapun hasil uji coba terbatas (uji proses) yang dilaksanakan di kelas V SD Negeri 3 Tilango memperoleh hasil sangat bagus dari guru maupun peserta didik. Dengan demikian, hasil pengembangan E-Modul Pencegahan Kekerasan di Sekolah Dasar dinyatakan sangat layak digunakan, serta dipercaya dapat mencegah perilaku perundungan, kekerasan seksual, dan intoleransi, untuk meningkatkan kualitas pendidikan.